The Tensile Properties of Uncoated and TiO2 Coated Bombyx Mori Silk Yarns Exposed to Thermal Treatment - Aksakal, Baki; Koc, Kenan (TAYLOR & FRANCIS INC, 2013)
Bombyx mori silk yarns were coated with a TiO2 network by sol-gel processing. The tensile properties of TiO2 coated silk yarns heated at various temperatures were examined and compared with those of uncoated silk yarns. The thermal properties of uncoated silk yarns and TiO2 coated silk yarns were also discussed. Prominent changes were seen in the rigidity and Young's modulus. The Young's modulus of TiO2 coated silk yarn increased by 13% at room condition and remained higher than that of uncoated silk yarns with increasing temperature. The shape of the stress-strain curve of TiO2 coated silk yarns became the same as uncoated silk yarns and showed a similar tendency of change to uncoated silk yarns with increasing temperature. The rupture values of uncoated silk yarns and TiO2 coated silk yarns decreased significantly, e.g., the breaking extension decreased from 17.28 to 2.44% and from 15.25 to 1.96% for uncoated silk yarns and TiO2 coated silk yarns, respectively, when the temperature was increased from 25 to 225 degrees C. Structural changes and degradation processes due to thermal effects for both uncoated and TiO2 coated silk yarns are discussed.
Keywords: beta-sheet microcrystals; silk yarn; stress-strain curve; tensile properties; titanium dioxide; Young's modulus; MECHANICAL-PROPERTIES; FIBROIN; FILMS; PEPTIDES; IR; Polymer Science